Immunohistochemical expression of basic fibroblast growth factor-2 and Heparanase in salivary pleomorphic adenoma - Riyadh N Mashkoor; Ahlam H Majeed; Nadia S Yas (College of Dentistry/ University of Baghdad, 2014)
Background: The aim of this study was to evaluate the expression of fibroblast growth factor-2 and Heparanase in salivary pleomorphic adenoma, and to correlate the two studied markers with each other and with clinicopathological parameters including: age, sex, tumor site and histopathological presentation. Methods: Sections of twenty five formalin-fixed paraffin embedded tissue blocks specimens of salivary pleomorphic adenoma were immunostained using monoclonal antibodies (Fibroblast growth factor-2 and Heparanase) to assess their expression in this tumor. Results: The expression of fibroblast growth factor-2 and Heparanase were positive in all pleomorphic adenoma cases (100%). The positive expression of fibroblast growth factor-2 was significantly correlated with histopathological presentation (p-value=0.032), but it was non-significantly correlated with FGF-2 and other clinicopathological parameters (age, sex, tumor site). The positiveexpression of Heparanse was non-significantly correlated with the histopathological presentation (p-value=0.088) as well as with other clinicopathological parameters (age, sex, tumor site). Statistically significant correlation was found between the expressions of both studied markers (p-value= 0.0005). Conclusion: The fibroblast growth factor-2 and Heparanase positive expression was noted in all cases of salivary pleomorphic adenoma signifying that both fibroblast growth factor-2 and Heparanase might contribute in the biological behavior of pleomorphic adenoma. The highly significant correlation found in the expression of both markers suggests their synergistic and cooperative role in the tumorigenesis of pleomorphic adenoma.